2021
DOI: 10.1007/s12013-021-00980-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemotherapy for Metastatic Colorectal Cancer on the TGF-β Signaling and Related miRNAs hsa-miR-17-5p, hsa-miR-21-5p and hsa-miR-93-5p

Abstract: Metastatic colorectal cancer (mCRC) patients are treated with standard chemotherapeutic drugs in the form of FOLFOX and FOLFIRI regimens. There are no reliable markers that could predict response to chemotherapy for mCRC. TGF-β signaling which interacts with microRNA (miRNA) network has important roles in tumor progression and chemotherapy resistance, thus the interplay between TGF-β signaling and miRNAs could be crucial for treatment response. The aim of this study was to analyze the effect of chemotherapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
8
2
Order By: Relevance
“…We have showed that 250 µg/ml bevacizumab alone or in combination with FOX does not influence miR-93-5p expression in SW620 cells. In this study, miR-93-5p expression was stable even under FOX which is in contrast to our previous findings were miR-93-5p expression was downregulated after 72 h of treatment with FOX in the same cell line [30]. The only difference in the two experimental settings was the endogenous control used, RNU6B which was used in the previous study and miR-16-5p which was used here, although both endogenous controls have been previously reported to ha normalization in SW620 cells [61,37].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We have showed that 250 µg/ml bevacizumab alone or in combination with FOX does not influence miR-93-5p expression in SW620 cells. In this study, miR-93-5p expression was stable even under FOX which is in contrast to our previous findings were miR-93-5p expression was downregulated after 72 h of treatment with FOX in the same cell line [30]. The only difference in the two experimental settings was the endogenous control used, RNU6B which was used in the previous study and miR-16-5p which was used here, although both endogenous controls have been previously reported to ha normalization in SW620 cells [61,37].…”
Section: Discussioncontrasting
confidence: 99%
“…(5-FU) (EBEWE Phar aliplatin (Actavis, Italy), as reported previously [30] or with 3 clinically relevant concentrations of bevacizumab (Avastin®, Roche, Switzerland) based on its clinical pharmacokinetics analysis: 25 µg/ml (concentration below steady-state), 85 µg/ml (steadystate concentration) [32,33] and 250 µg/ml (average concentration of maximal plasma concentration reported in Liston et al [34] and Zhi et al [33] or with a FOX/bevacizumab combinations.…”
Section: Subjectssupporting
confidence: 67%
See 2 more Smart Citations
“…Among the miRNAs significantly overexpressed in CCCO cells, miR-21-5p is one of the first identified miRNAs and has been extensively studied as a representative molecule [45]. Previous studies have shown that the plasma level of exosomal miR-21-5p could be used as a biomarker for several cancers, including breast [46] and colorectal [47] cancers and gastric cancer in young patients [48]. MiR-21 is significantly upregulated in endometriosisassociated ovarian cancer, which is characterized by decreased expression of PTEN [49], a well-known tumor suppressor whose inactivation is an early event of malignant transformation from endometriosis [50].…”
Section: Detection Of Exosomal Mirna Highly Expressed In Ccco Compare...mentioning
confidence: 99%